Mathematical models based on difference and differential equations for dengue disease mapping in Bandung Indonesia - Farah Kristiani (Tanjong Malim, 2019)
Mathematical models based on difference and differential equations for dengue disease mapping in Bandung Indonesia by Farah Kristiani